STRATEGI PENINGKATAN MUTU PERGURUAN TINGGI AGAMA ISLAM BERBASIS BALANCED SCORECARD - dkk., Machasin (WALISONGO, 2011)
Abstract Â  This study is a policy research, which use STAIN in Central Java as objects of research, while faculty, students, employees, officers and graduates of the unit being analyzed. The analysis technique used is exsploratif descriptive. To implement the balanced scorecard at STAIN would require accurately data and documents, it is to be aware of changes in key indicators that can be used as the basis of evidence the organizationâs activities. In this study, the perspective which used is the perspective of stakeholders, administrative and financial management, and the teaching and learning process, work ethos, culture and good governance. The results of the five perspective are refered to the differences of implementation, but for administrative and financial management perspective STAIN, in Central Java, faced the same thing that is the not optimal care units so that are still limited contribution to STAIN revenue. Â  *** Kajian ini merupakan kajian kebijakan, yang menggunakan STAIN di Jawa Tengah sebagai obyek penelitian, dengan pejabat fakultas, mahasiswa, pegawai, dan lulusan yang menjadi obyek analisis. Teknik analisis yang digunakan adalah deskriptif eksploratif, dengan perspektif stakeholder, pejabat administratif dan keuangan, proses belajar mengajar, etos kerja, budaya, dan dan good governance. Hasil dari lima perspektif ini menunjukkan adanya perbedaan implementasi, sementara dari perspektif pengelola administrasi dan keuangan menghadapi masalah yang sama yaitu tidak optimalnya unit-unit perawatan sehingga masih kecil kontribusinya bagi perolehan STAIN. Â  Keywords: balanced scorecard, mutu PTAI, STAIN